Conciencia ambiental en el uso doméstico del agua del Río Amazonas de la comunidad de San Felipe, Loreto, 2024 - Lozano Rocha, Fabio Andre (2025)
The study, of a descriptive, analytical, transversal and quantitative type, with a non experimental design, evaluated the influence of environmental awareness on the domestic use of water from the Amazon River in the community of San Felipe. A census was carried out on 20 homes using a structured survey based on five dimensions: affective, cognitive, conative, active and behavioral, with a Likert scale. The instrument showed good reliability (α = 0.795) and a normal distribution of the data (Shapiro-Wilk), which allowed the Pearson correlation to be applied. There is a high level of environmental awareness in the community, with a positive influence on the domestic use of water, highlighting the affective and conative dimensions. The affective and active dimensions are strong, reflecting an emotional commitment and concrete actions towards sustainability. However, the cognitive dimension presents deficiencies, which limits technical knowledge on water management and conservation. The use of water from the Amazon River is essential for daily activities such as washing, cooking and hygiene, although many practices lack adequate treatment, exposing the population to health risks. Likewise, the lack of technical knowledge and resources makes it difficult to assess risks related to water quality. It is recommended to implement educational and community programs to strengthen knowledge and sustainable practices, since the relationship between environmental awareness and water use shows that higher levels of awareness lead to more responsible management of water resources.